Citizenship Challenges in Myanmar’s Democratic Transition: Case Study of the Rohingya-Muslim - Suaedy, Ahmad; Hafiz, Muhammad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2015)
As a part of the Myanmar transition to democracy, which began after the election in 2010, the census on March-April 2014 refused to count the Rohingya ethnic group. This was symbolic of the Myanmar government’s rejection of Rohingya people as citizens. The paradox is that democracy necessitates a guarantee of fundamental freedoms and recognition of all group identities. Through in depth interviews with a number of Rohingya political and social leaders at the end of March 2014, in Yangon, this research details the Rohingya struggle to secure their rights in the political process. A number of documents both from the Rohingya and from the Myanmar government justify why and how the process of exclusion and discrimination occurs. This research will conclude with a discussion of the challenges and recommended steps for the future to accommodate the Rohingya as Myanmar citizens, and of the need for international and regional support.DOI: 10.15408/sdi.v22i1.1387